Yogyakarta and Its Special Fascination: Iconic Landmarks, Memories, Hopes, and Challenges - Sadana, Agus S; Prasetya, L Edhi; Dharmaraty , Ashri Prawesthi; Wibisono , Adryanto Ibnu; Adi, Swambodo M (RUSTIC, 2025)
This study discusses the Tugu Pal Putih as a symbol of cultural identity and branding of the city of Yogyakarta through visual elements, expressions, and discussions on Instagram social media. The research was carried out qualitatively with a netnography approach and visual analysis of Instagram content related to this cultural landmark. The analysis is done through a thematic coding process to identify dominant themes and patterns reflecting public perceptions. The study results show that Tugu Pal Putih is not just a physical landmark but also a symbol of pride that forms a collective memory and emotional connection to Yogyakarta's atmosphere. Themes such as longing, ideal city, and pride reflect strong public attachment. Despite its distinctiveness, issues like hot weather and traffic congestion present challenges that require adaptive strategies. The integration of cultural, visual, and emotional elements enhances city identity and supports effective city branding. These findings offer insight for branding management to maintain the uniqueness of Yogyakarta as a cultural place.